A Descriptive Study of Colorectal Cancer in Hiwa Cancer Hospital, Sulaymaniyah, Iraq - Mahmood, Kochar I.; Namiq, Kadhim F.; Muhamad, Chovin A.; Muhamad, Begard O.; Majed, Kurdistan M.; Fattah, Hana N. (Science Journal of University of Zakho, 2017)
Colorectal cancer is the third most common cancer and the fourth leading cause of death from cancer worldwide. This study provides an overview of changes in sociod-demographic parameters in patients with colorectal cancer (henceforth CRC) disease in a local cancer hospital in Sulaymaniyah province of Kurdistan region of Iraq. The study included 113 patients admitted to Hiwa Cancer Hospital, Sulaymaniyah from January 2014 to December 2015. The data collection lasted for 3 weeks (from 19/12/2015 to 11/01/2016) and was obtained from the management department of Hiwa Cancer Hospital. Several socio-demographic parameters including age, gender, and smoking, as well as biochemical parameters such as liver function, renal function and blood glucose level were studied and statistically analyzed. Results have shown that the majority of CRC patients were neither current smoker nor x-smoker (P-value < 0.05). Males suffered from CRC at an earlier age compared to females (P-value < 0.05). Regarding the biochemical tests, there was no significant correlation between CRC and impaired liver function during the diagnosis process and most of the study patients had a normal liver function test on presentation. In contrast, the correlation between CRC and impaired renal function on presentation was statistically siginificant (P-value < 0.05). No significant difference was noted in the means of hematological and biochemical parameters between males and females, except for white blood cells and serum Aspartate Aminotransferase. White blood cells and total serum bilirubin showed significant differences (P-value < 0.05) between smoker and nonsmoker sub-populations. It was concluded that CRC is one of the common cancers in Sulaymaniyah province. Males develop it at an earlier age compared to females, and the impaired renal function is a significant finding on presentation.